Teknik, Metode Dan Ideologi Penerjemahan Arab-Indonesia Dalam Terjemahan Buku Manzhumah Al-Qawāid Al-Fiqhiyyah Karya Syeikh Abdurrahman Bin Nashir As-Sa’Diy - Thalhah As Salafy (Uktub: Journal of Arabic Studies, 2021)
This research aims to: (1) describe the techniques of translation applied by the translator in the translation books Manzhumah Al-Qowaid Al-Fiqhiyyah, (2) describe the methods and ideology of translation applied by the translator in the translation books Manzhumah Al-Qowaid Al-Fiqhiyyah. The method used in this research is a qualitative descriptive qualitative method. The source of the data in the form of a translation of the book Manzhumah Al-Qowaid Al-Fiqhiyyah. The researcher assumes that in 49 bait nazham poems there are the application of translation techniques, methods, and ideologies in the form of word, phrase, clause, and sentence. Data analysis was done gradually; first, classifying translation techniques. Second, observing from the application results in the dominant translation technique than to determine the used translation method. Third, analyzing the translation ideology based on the technique result and method applied by the translator. The results of this study showed that there were 16 techniques of translation, of the 115 data which is applied by the translator in the translation of the book Manzhumah Al-Qowaid Al-Fiqhiyyah with the details of the 4 techniques oriented to the source language and 12 techniques oriented to the target language. Techniques that are oriented to the source language are 7 pure borrowings, 4 calke, 20 literal translation, and 5 naturalized borrowing. While the techniques are oriented to the target language are 32 addition, 12 transpositions, 6 descriptions, 5 reductions, 6 linguistic amplification, 4 compensation, 3 particularizations, 3 discursive creation, 3 establish equivalence, 2 adaptation, 2 modulations, 1 generalization. Based on these techniques, then there is a translation of the 36 data are oriented on the source language and the translation of the 78 data are oriented on the target language. The method of translation applied is a method that emphasizes the target language, namely the method of communicative translation. Based on these methods, the ideology that is applied is the ideology of domestication